Experiences of the beneficiaries of Interactive Popular Theatre (IPT): a qualitative study on the experiences of the beneficiaries of IPT as a part of BRAC CST program on COVID-19 prevention at Cox’s Bazar Sadar, Ramu & Chakoria upazila in Bangladesh - Rahman, Md. Mizanur (Brac University, 2023)
This project report is submitted in partial fulfillment of the requirements for the degree of Master of Public Health (MPH), 2023.